Influence of NQO1 Polymorphisms on Warfarin Maintenance Dose: A Systematic Review and Meta-Analysis (rs1800566 and rs10517). (12th August 2021) - Tian, Lihong; Xiao, Pingping; Zhou, Bingrong; Chen, Yishan; Kang, Lijuan; Wang, Qingqing; Lin, Jianfeng; Son, Min; Wu, Qingxiu
Abstract : This meta-analysis was conducted to analyze the effect of NQO1 polymorphism on the warfarin maintenance dosage. Using strict inclusion and exclusion criteria, we searched PubMed, EMBASE, and the Cochrane Library for eligible studies published prior to July 7, 2021. The required data were extracted, and experts were consulted when necessary. Review Manager Version 5.4 software was used to analyze the relationship between NQO1 polymorphisms and the warfarin maintenance dosage. Four articles involving 757 patients were included in the meta-analysis. Patients who were NQO1 rs10517 G carriers (AG carriers or GG carriers) required a 48% higher warfarin maintenance dose than those who were AA carriers. Patients with NQO1 rs1800566 CT carriers required a 13% higher warfarin dose than those who were CC carriers, with no associations observed with the other comparisons of the NQO1 rs1800566 genotypes. However, the results obtained by comparing the NQO1 rs1800566 genotypes require confirmation, as significant changes in the results were found in sensitivity analyses. Our meta-analysis suggests that the NQO1 rs10517and NQO1 rs1800566 variant statuses affect the required warfarin maintenance dose.